A rare case of CD1a‐negative Langerhans cell histiocytosis of the central nervous system in a child. Issue 10 (1st September 2017) - Powell, Priscilla; Vitug, Gaile; Castro‐Silva, Fernando; Ray, Anish
Key Clinical Message: Langerhans cell histiocytosis is a dendritic cell disorder with a wide spectrum of severity and presentations. Histopathology typically demonstrates a proliferation of Langerhans cells and a lymphohistiocytic inflammatory infiltrate with eosinophils. The diagnosis is supported by immunohistochemistry with the cell markers S100, CD1a, CD68, and Langerin [ Blood, 126, 2015, 26 and N Engl J Med, 331, 1994, 154]. Abstract : Langerhans cell histiocytosis is a dendritic cell disorder with a wide spectrum of severity and presentations. Histopathology typically demonstrates a proliferation of Langerhans cells and a lymphohistiocytic inflammatory infiltrate with eosinophils. The diagnosis is supported by immunohistochemistry with the cell markers S100, CD1a, CD68, and Langerin [ Blood, 126, 2015, 26 and N Engl J Med, 331, 1994, 154].